1986
DOI: 10.1093/nar/14.12.4719
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the human ghicagon gene

Abstract: A clone containing the complete human glucagon gene was isolated and sequenced. The gene is approximately 9.4 kilobases in length and comprises six exons and five introns. The putative preproglucagon encoded by this gene, 180 amino acids in length and containing glucagon and two glucagon-like peptides, is very similar to that of other mammalian species (greater than 90% amino acid sequence homology). There is 88% nucleotide sequence homology between the proximal 130 base pairs of the 5' flanking regions of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0

Year Published

1987
1987
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(62 citation statements)
references
References 26 publications
1
61
0
Order By: Relevance
“…Specifically, a sequence identical to that of the core sequence of the PAX6 paired domain consensus recognition site (Epstein et al 1994) was found at position -262 to -248 bp relative to the start site of transcription of the rat glucagon gene (Fig. 3A), and is also conserved in the h u m a n glucagon promoter (White and Saunders 1986). This sequence is part of the A site of the glucagon G3 promoter element, which is similar to sequences also found in the rodent insulin I and insulin II and somatostatin promoters, and therefore has been referred to as the pancreatic islet cell (n = 27) (n = 10) 12.2 • 1.3 9.1 • 0.92 (75%) 1.6 • 0.08 (13%) (n = 11) (n = 27) (n = 10) 74.4 • 4.0 74.5 • 9.7 (100%) (n = 6) (n = 6) 57.3 x 106 + 12.5 x 106 (8%) 34.1 x 106 + 5.7 x 106 (60%) 4.58 X 10 6 + 0.94 x 106 (n = 6) (n --14) (n = 6) aThe average number of glucagon-or insulin-positive cells per section (as detected by immunohistochemical staining) was determined by counting stained cells in eight sections from an individual pancreas (approximately every twentieth section).…”
Section: Pax6 Binds To Glucagon Insulin and Somatostatin Gene Regulmentioning
confidence: 90%
“…Specifically, a sequence identical to that of the core sequence of the PAX6 paired domain consensus recognition site (Epstein et al 1994) was found at position -262 to -248 bp relative to the start site of transcription of the rat glucagon gene (Fig. 3A), and is also conserved in the h u m a n glucagon promoter (White and Saunders 1986). This sequence is part of the A site of the glucagon G3 promoter element, which is similar to sequences also found in the rodent insulin I and insulin II and somatostatin promoters, and therefore has been referred to as the pancreatic islet cell (n = 27) (n = 10) 12.2 • 1.3 9.1 • 0.92 (75%) 1.6 • 0.08 (13%) (n = 11) (n = 27) (n = 10) 74.4 • 4.0 74.5 • 9.7 (100%) (n = 6) (n = 6) 57.3 x 106 + 12.5 x 106 (8%) 34.1 x 106 + 5.7 x 106 (60%) 4.58 X 10 6 + 0.94 x 106 (n = 6) (n --14) (n = 6) aThe average number of glucagon-or insulin-positive cells per section (as detected by immunohistochemical staining) was determined by counting stained cells in eight sections from an individual pancreas (approximately every twentieth section).…”
Section: Pax6 Binds To Glucagon Insulin and Somatostatin Gene Regulmentioning
confidence: 90%
“…Interestingly, no such consensus sequence was detected in the 5' flanking region of the human glucagon gene (5 respectively (36,37). These regulatory peptides are known to exert their effects through cyclic AMP-and protein kinase GLI as both intact fetal intestine and adult C-dependent pathways, respectively (28,38).…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of the cDNAs and genes that encode proglucagon (3)(4)(5)(6) has shown that this prohormone resembles other polyproteins in that it encodes multiple peptides separated from each other by pairs of basic amino acids characteristic of the sites commonly cleaved by prohormone-processing enzymes. Posttranslational processing of proglucagon is also highly tissue-specific, with the liberation of glucagon in the pancreas and glicentin and the glucagon-like peptides in the intestine (7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…Comparison of the 5'-flanking sequences of the rat and human glucagon genes indicates that Gl and G2 have been highly conserved throughout evolution, with 95 and 97% homology, respectively (42) (Fig. 8).…”
Section: Discussionmentioning
confidence: 99%